Strategic management in third sector organizations: an overview of the Portuguese social solidarity cooperatives - Simaens, Ana Margarida (2015)
The increasing importance that the Third Sector has been gaining in the societies and the economies raises the need to ensure not only for its survival, but mainly its development and growth. The border that separates the so-called for-profits and nonprofit organizations has then become more tenuous considering strategic management. The study aims to know the management practices in this domain in Portugal. To which extent its action is thought beyond the short term, which is the degree of formalization and how the strategic management process is developed are the questions we intend to study. Thus, an empirical study has been developed, circumscribed to the social solidarity cooperatives. From this analysis, it has resulted that in general these organizations do not develop a clear strategic management process and, besides thinking in the future, there is still some lack of formalization. Nevertheless, the way to go is somehow facilitated by the openness that the organizations reveal to apply new strategic management practices. The case study analysis provides the comprehension of the challenges these organizations face. These are related to three issues that, in general, are common to the others: the need for additional sources of funding, the need for strategic management and the need for internal organization, that is to say, to think the organization in a global way. This dissertation ends with the proposal of the Balanced Scorecard as a strategic management tool that is especially useful for third sector organization in the resolution of these and other challenges.